(3eUGQY GdeUGQYs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3eMeO Hf YHO GdcQje Hf CMeO GdTgQSJGfj,J (B548 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf aEfi dTZai HGdYdhe GdYbdjI hGdeYGQa GdjbjfjI aYKQJ ai CKfGA WdHi Ydi cJGH jYQa HGdeUGQYGJ ddTjN JGL GdOjf CHh GdaJM eMeO Hf YHO GdcQje GdTgQSJGfi aQCjJ Cf CcTa Yf JehjgGJg s
(3BNQgG (B:s
(3hGddg jYUefG ef GdEYJbGO GdHGWd hGdbhd GdZjQ eWGHb Efg edge GdYbd hedbf GdUhGH efg GdeHOC hEdjg GdeBH s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(2956) s
Keywords: (3GdJhMjO hGdedd hGdfMds